2021
DOI: 10.1016/j.aucc.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

The use of altered rapid response calling criteria in a tertiary referral facility

Abstract: Purpose:The purpose of this study was to examine the current utilisation of altered rapid response call criteria (ARRCC) at a tertiary hospital. Methods :A retrospective review of all acute care admissions across 17 months was undertaken using the hospital administration system and electronic medical record to identify patients with ARRCC. In patients with altered criteria, the type of alteration, frequency of rapid response call, cardiac arrest, intensive care admission and death in hospital were identified.C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…In a more recent study (also conducted in Australia) similar findings were reported, whereby patients with adjusted criteria more frequently triggered an efferent limb activation, more frequently had a cardiac arrest and more frequently died in hospital compared to patients with standard (i.e. unmodified) criteria (Crouch et al, 2020). These findings highlight the potential vulnerability of the sub‐group of patients likely to have response criteria modified, the potential safety implications of reducing the level of response and the complexity of the clinical decisions that underpin these adjustments.…”
Section: Discussionsupporting
confidence: 53%
“…In a more recent study (also conducted in Australia) similar findings were reported, whereby patients with adjusted criteria more frequently triggered an efferent limb activation, more frequently had a cardiac arrest and more frequently died in hospital compared to patients with standard (i.e. unmodified) criteria (Crouch et al, 2020). These findings highlight the potential vulnerability of the sub‐group of patients likely to have response criteria modified, the potential safety implications of reducing the level of response and the complexity of the clinical decisions that underpin these adjustments.…”
Section: Discussionsupporting
confidence: 53%
“… 29 A retrospective, single-centre study identified that nearly one-quarter of alterations to the MET criteria were made by junior doctors, and that altered MET trigger criteria were significantly associated with ICU admission, in-hospital cardiac arrest and in-hospital death. 30 Our findings reiterate that great care must be taken when altering MET criteria.…”
Section: Discussionmentioning
confidence: 56%
“…5 In prospective data, the prevalence of discharge home after receiving RRS activation was approximately 50%, consistent with our results, while the prevalence of discharge home after hospitalization was 86.8%. 5 , 12 These results indicate that adverse events were associated with less frequency of discharge home. There might be several reasons for the low frequency of discharge home after hospitalization.…”
Section: Discussionmentioning
confidence: 85%
“…Few published reports describe the outcomes of patients with adverse events who required RRS activation and were discharged home 5 . In prospective data, the prevalence of discharge home after receiving RRS activation was approximately 50%, consistent with our results, while the prevalence of discharge home after hospitalization was 86.8% 5,12 . These results indicate that adverse events were associated with less frequency of discharge home.…”
Section: Discussionmentioning
confidence: 99%